Enhanced Macroanion Recognition of Superchaotropic Keggin Clusters Achieved by Synergy of Anion–π and Anion–Cation Interactions. Issue 70 (11th November 2020) - Qi, Bo; An, Sai; Luo, Jiancheng; Liu, Tianbo; Song, Yu‐Fei
Abstract: Keggin clusters are the most widely used polyoxometalate building blocks for the construction advanced materials, but effective methods for precisely recognizing the isostructural analogues of Keggins are still limited. In this study we employed the zwitterionic molecule 4, 4′‐dipyridyl N, N′ ‐dioxide as a recognition receptor to specifically bind to the three Keggin analogues PW12 O40 3−, PMo12 O40 3−, and SiW12 O40 4−, which separately co‐assembled into three different types of spherical charged colloids of different sizes. The recognition phenomena were confirmed by electrochemical methods and their crystallization behavior. Compared with solely anion–cation interaction‐driven systems, the synergism with the anion–π interactions between the superchaotropic Keggins and the electron‐deficient pyridine rings is believed to enhance the recognition. This observation is intriguing as the long‐range solution assembly of Keggins is mainly driven by short‐range anion–π interactions. Our results show that the little‐noticed hydration shell of Keggins is significantly influenced by the superchaotropic effect, leading to differentiated binding affinity to the receptors and more obvious recognition phenomena between tungsten/molybdenum Keggin analogues. Abstract : Now well recognized ! The two most widely used, highly similar Keggin macroanions are well recognized by the zwitterionic molecule 4, 4′‐dipyridyl N, N′ ‐dioxide to co‐assemble into different sized colloids. The synergistic relationship between the superchaotropic effect and acid strength of the Keggin clusters is revealed in this recognition study.